Gender norms associated with adolescent sexual behaviours in Uganda. Issue 231 (21st May 2019) - Nalukwago, Judith; Crutzen, Rik; van den Borne, Bart; Bukuluki, Paul Mukisa; Bufumbo, Leonard; Burke, Holly McClain; Field, Samuel; Zikusooka, Amos; Fiedler, Anne Akia; Alaii, Jane
Abstract: The relationship between gendered power relations and sexual behaviours of adolescents has been limitedly explored in Uganda. A 2015 cross‐sectional survey covering 16 purposively selected districts of Uganda assessed perceptions and associations of gender norms measured using the Gender Equitable Men scale and sexual behaviours among adolescents (N = 867). Findings indicate that behavioural intention to use contraception was moderately correlated with a gender equitable norm towards reproductive health and pregnancy and disease prevention among girls, r = .23 (p < .01; 95% CI .14‐.31) and boys, r = .22 (p < .01; 95% CI .12‐.31). A moderate correlation was found between self‐efficacy to use condoms and the norm towards reproductive health and pregnancy and disease prevention among girls, r = .29 (p < .01; 95% CI .20‐.37) and boys, r = .30 (p < .01; 95% CI .21‐.38). This indicates persistent inequitable gender norms that affect health service uptake among adolescents. Addressing inequitable gender norms requires working closely with girls and boys, promoting informed peer and partner discussions, engaging in strategic partnerships with parents, religious, political, and community leaders, and enforcing health information services to address misconceptions.